If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+(5X-6)=12
We move all terms to the left:
X+(5X-6)-(12)=0
We get rid of parentheses
X+5X-6-12=0
We add all the numbers together, and all the variables
6X-18=0
We move all terms containing X to the left, all other terms to the right
6X=18
X=18/6
X=3
| 5x-2/4-7=0 | | t^2-40*t-100=0 | | 3x-1/5=x+1/3 | | 17=2(2x=9) | | 20=13x-8 | | (x-3)(x-2)=2x | | 9x-3=5x+6 | | 1h+60=2h+180 | | (4x+6)(x+1)=0 | | 26+5r=9r | | 10(k-90)=90 | | 1/2(8x+10)=1/3(12x-21) | | 1/4r=3 | | 90=10(k–90) | | X+5/4x=90 | | 12/54=18/x | | -(s+-52)=27 | | 5+5/4x=90 | | 18/x=12/54 | | -3/11m=1/5 | | 21=x/4+15 | | 12/18=54/x | | 3x=28+x | | 5w+3-w=10+w+2 | | 1-(x-3)=x+4 | | 2x-(4x+2)=6x+14 | | X+15=1x-7 | | d/7–1=2 | | 3(3x-7)=-72+52 | | -5a-9+a=45/3 | | -2x(x-3)=-3(-8) | | X+4/3-x-4/5=2+3x-1/15 |